Ketamine prolongs survival in symptomatic SOD1-G93A mice - Stanford, John A.; Macaluso, Matthew; Barohn, Richard J. (RRNMF Neuromuscular Journal, 2021)
Objective. Although riluzole and edaravone are FDA-approved for Amyotrophic Lateral Sclerosis (ALS), these drugs have negligible effect on disease progression and survival. Recent studies reporting neuroprotection from sub-anesthetic doses of ketamine support testing this drug in this rapidly progressing and fatal disease.    Methods. We administered ketamine at 0, 10, and 30 mg/kg to SOD1-G93A mice 5 days/week beginning at 90 days of age. We measured body weight, grip strength, and survival in this model of ALS.    Results. Although ketamine did not influence disease-related loss of body weight, it did delay grip strength declines in the 30 mg/kg group. Ketamine also prolonged survival in the 30 mg/kg group and dose-dependently increased the latency between 20% loss of body weight and death.    Conclusions. These results support further testing of ketamine in preclinical models of ALS to determine optimal dosing. They also support testing in the clinic given the limited efficacy of current ALS treatments and given FDA approval of ketamine for other indications like treatment-resistant depression.